(untitled) (Archaeologia Adriatica, 2018)
Glass lamps belong to a number of (late) medieval and post-medieval interiors on the eastern Adriatic coast. They were used to light modest country churches, exuberant city cathedrals, and to less extent profane, primarily residential buildings. In addition to an example of a “bell-shaped” lamp (conical body with elongated hollow handle on the bottom), group of lamps from the area of historical core of Zadar consists of biconical lamps with handles for suspension, known as Islamic or Oriental lamps. They have been dated to the period from the end of the 14th to the beginning of the 16th century. Although fragmented, they are well preserved and they definitely represent an important indicator of typological presence of this everyday object in the Dalmatian littoral.